The continuously evolving phenotype of succinic semialdehyde dehydrogenase deficiency - Julià-Palacios, Natalia; Kuseyri Hübschmann, Oya; Olivella, Mireia; Pons, Roser; Horvath, Gabriella; Lücke, Thomas; Fung, Cheuk-Wing; Wong, Suet-Na; Cortès-Saladelafont, Elisenda; Rovira-Remisa, M. Mar; Yıldız, Yılmaz; Mercimek-Andrews, Saadet; et al. (Journal of inherited metabolic disease, 2024)
The objective of the study is to evaluate the evolving phenotype and genetic spectrum of patients with succinic semialdehyde dehydrogenase deficiency (SSADHD) in long-term follow-up. Longitudinal clinical and biochemical data of 22 pediatric and 9 adult individuals with SSADHD from the patient registry of the International Working Group on Neurotransmitter related Disorders (iNTD) were studied with in silico analyses, pathogenicity scores and molecular modeling of ALDH5A1 variants. Leading initial symptoms, with onset in infancy, were developmental delay and hypotonia. Year of birth and specific initial symptoms influenced the diagnostic delay. Clinical phenotype of 26 individuals (median 12 years, range 1.8-33.4 years) showed a diversifying course in follow-up: 77% behavioral problems, 76% coordination problems, 73% speech disorders, 58% epileptic seizures and 40% movement disorders. After ataxia, dystonia (19%), chorea (11%) and hypokinesia (15%) were the most frequent movement disorders. Involvement of the dentate nucleus in brain imaging was observed together with movement disorders or coordination problems. Short attention span (78.6%) and distractibility (71.4%) were the most frequently behavior traits mentioned by parents while impulsiveness, problems communicating wishes or needs and compulsive behavior were addressed as strongly interfering with family life. Treatment was mainly aimed to control epileptic seizures and psychiatric symptoms. Four new pathogenic variants were identified. In silico scoring system, protein activity and pathogenicity score revealed a high correlation. A genotype/phenotype correlation was not observed, even in siblings. This study presents the diversifying characteristics of disease phenotype during the disease course, highlighting movement disorders, widens the knowledge on the genotypic spectrum of SSADHD and emphasizes a reliable application of in silico approaches.